Open University and Distance Education Coordination: Strategies used to consolidate distance education at the National Autonomous University of Mexico - Berruecos, Citlalli (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
This case study describes three main strategies used from March 2002 to November 2003 at the Open University and Distance Education Coordination (CUAED) of the National Autonomous University of Mexico (UNAM) to consolidate distance education at the University. The author explains how, in just 18 months, these three main strategies enabled the UNAM to emerge as model of distance education for other public and private institutions in Latin America.Distance education in Latin America, rather than being considered a second rate educational complement for traditional higher education, must be seen as a fundamental engine for restructuring other university systems, especially the public ones (Casas Armengol, 2002).. . . the widespread use of new technologies in an organization does constitute a major cultural change. Furthermore, for such change to be successful, leadership of the highest quality is required (Bates, 2000).